Menstrual health and period poverty among young people who menstruate in the Barcelona metropolitan area (Spain): protocol of a mixed-methods study - Medina-Perucha, Laura; Jacques-Aviñó, Constanza; Valls-Llobet, Carme; Turbau-Valls, Rosa; Pinzón, Diana; Hernández, Lola; Canseco, Paula Briales; López-Jiménez, Tomàs; Lizarza, Enara Solana; Feliu, Jordina Munrós; Berenguera, Anna (BMJ Open, 2020)
Introduction The importance of menstrual health has been historically neglected, mostly due to taboos and misconceptions around menstruation and androcentrism within health knowledge and health systems around the world. There has also been a lack of attention on ‘period poverty’, which refers to the financial, social, cultural and political barriers to access menstrual products and education. The main aim of this research is to explore menstrual health and experiences of period poverty among young people who menstruate (YPM). Methods and analysis This is a convergent mixed-methods study, which will combine a quantitative transversal study to identify the prevalence of period poverty among YPM (11–16 years old), and a qualitative study that will focus on exploring menstruation-related experiences of YPM and other groups (young people who do not menstruate (YNM); primary healthcare professionals; educators and policy-makers). The study will be conducted in the Barcelona metropolitan area between 2020 and 2021. Eighteen schools and 871 YPM will be recruited for the quantitative study. Sixty-five YPM will participate in the qualitative study. Forty-five YNM and 12 professionals will also be recruited to take part in the qualitative study. Socioeconomic and cultural diversity will be main vectors for recruitment, to ensure the findings are representative to the social and cultural context. Descriptive statistics will be performed for each variable to identify asymmetric distributions and differences among groups will be evaluated. Thematic analysis will be used for qualitative data analyses Ethics and dissemination Several ethical issues have been considered, especially as this study includes the participation of underage participants. The study has received ethical approval by the IDIAPJGol Research Ethics Committee (19/178 P). Research findings will be disseminated to key audiences, such as YPM, YNM, parents/legal tutors, health professionals, educators, youth (and other relevant) organisations, general community members, stakeholders and policy-makers, and academia.
Keywords: 2000 à aujourd'hui; 2020-2029; adolescentes*; discipline; espagne; europe; médecine; projet charge mentale; périodes historiques; régions géographiques; santé; santé menstruelle; santé publique; thématiques

Transidentité: de la théorie à la politique. Une métamorphose culturelle entre pragmatisme et transcendance - Espineira, Karine (L'information psychiatrique, 2011)
Du décret français du 10 février 2010 aux travaux de réécriture lancés par le DSM et la CIM, les questions transidentitaires doivent être discutées, appréhendées sur le plan théorique aussi bien que politique. Le schisme entre les associations d’usagers, les trans’ en demande et/ou en obligation de suivi, et les équipes hospitalières spécialisées dans la prise en charge de ce public, pour le cas de la France tout particulièrement, a une histoire intimement liée à un ordre présumé du social et de ses acteurs en termes de genre dans une vision binaire de la société. La demande de reconnaissance de savoirs, d’expertises du terrain transidentitaire s’est heurtée, dès le début des années 1980, au bouclier thérapeutique , que l’on peut définir comme l’argument ultime de l’instance médico-légale en charge du sujet transsexe, écartant les autres sujets/trajets trans’, pour mettre à distance toute intervention du politique, des sciences humaines et sociales dans ce qui est devenu un paradigme théorique : le changement de sexe est d’abord un changement culturel de genre. Enfin, l’instance médico-légale s’efforce d’ignorer sa propre politisation et militance. Partagé entre la volonté de résister et de participer face/avec un protocole inadapté, inefficace et culturellement obsolète, le terrain a connu ses propres mouvements s’interrogeant, s’interpellant sur l’esprit de la méthode. La question trans’ compte désormais autant de politiques que de groupes. La théorisation du fait trans’, trouve sa légitimité non pour revenir seulement sur l’inégalité homme/femme, mais pour lutter du même élan contre toute forme d’inégalité et de stigmatisation. Le terrain transidentitaire s’est profondément transformé, les outils pour l’appréhender comme le paradigme théorique lui-même, se doivent une chose : évoluer.
Keywords: 2000 à aujourd'hui; 2010-2019; LGBTQIA2+; approches et analyses; cours; discipline; europe; france; militance; premier cycle; psychiatrie; périodes historiques; queer; régions géographiques; santé; sciences; sciences humaines; soc2014; sociologie; thématiques; transféminisme; violences; violences médicales

Démédicaliser les corps, politiser les identités : convergences des luttes féministes et intersexes - Kraus, Cynthia; Perrin, Céline; Rey, Séverine; Gosselin, Lucie; Guillot, Vincent (Nouvelles Questions Féministes, 2008)
Number: 1
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; belgique; capacitisme; corps; cours; discipline; discours dominant; europe; france; féminisme interdisciplinaire; féminisme matérialiste; hétérosexisme; identités LGBTQIA2+; intersexuation; inégalités; luxembourg; marginalisation; militance; médecine; philosophie; premier cycle; psychiatrie; périodes historiques; queer; régions géographiques; santé; sciences; sciences humaines; soc2014; soc2051; sociologie; systèmes d'oppressions; thématiques; transféminisme; violences; violences médicales

Cerveau, sexe et idéologie - Vidal, Catherine (Diogène, 2004)
Keywords: 2000 à aujourd'hui; 2000-2009; approches et analyses; corps; cours; discipline; discours dominant; europe; fem1000; france; neurobiologie; premier cycle; psy4910; périodes historiques; ressource en ligne; régions géographiques; sciences; stéréotypes; systèmes d'oppressions; thématiques